Developing a Semi-Direct Speaking Test for Fourth Graders Using Video Conferencing - Yuditha Putri Wiwaharini; Bartholomeus Budiyono (Widya Mandala Surabaya Catholic University, 2022)
This study aimed to develop alternative English-speaking testing to be used during the COVID-19 pandemic. A semi-direct speaking test for 4 graders was the final product of this study. Cambridge curriculum with the ESL framework (0837) was used to formulate the test. It was designed using steps suggested by (Bachman and Palmer,1996). It also has been reviewed by an expert and a trial group. It asked each test-taker to tell a story using provided picture series, connectors, and past verbs within 5 minutes. A minute was given for them to study the picture series; the rest was to do the test. It was delivered by using video conferencing called Zoom. The result showed that the test developed was a valid, reliable, practical, and authentic measurement. Its reliability was proved by test-retest and interrater results. Its validity, practicality, and authenticity were proved by providing an expert judgement collected through questionnaires.